Case Report: Diagnosis and treatment of congenital right atrial dissection associated with atrial aneurysm - Zhang, Yuan-yuan; Zhou, Chi-heng; Shen, Qun-shen (Frontiers in Cardiovascular Medicine, 2025)
Spontaneous atrial dissection and atrial aneurysm are extremely rare conditions. This may be the first reported case diagnosed in the fetal period and successfully treated with surgery under extracorporeal circulation in infancy. Although the infant in this case underwent surgery successfully, recovered, and was discharged, the optimal timing for surgical intervention in such cases remains unclear. This report aims to provide a treatment reference for similar cases.